Salmonella typhimurium SA host specificity system is based on deoxyribonucleic acid-adenine methylation. - Hattman, S (1976)
We have determined the nature of the deoxyribonucleic acid (DNA) modification governed by the SA host specificity system of Salmonella typhimurium. Two lines of evidence indicate that SA modification is based on methylation of DNA-adenine residues. (i) The SA+ locus of Salmonella was transferred into Escherichia coli B, a strain that does not contain 5-methylcytosine in its DNA; although the hybrid strain was able to confer SA modification, its DNA still did not contain 5-methylcytosine. (ii) the N6-methyladenine content of phage L DNA was measured after growth in various host strains; phage lacking SA modification contained fewer N6-methyladenine residues per DNA. We also investigated the possibility, suggested by others (32), that SA modification protects phage DNA against restriction by the RII host specificity system. Phages lambda, P3, and L were grown in various SA+ and SA- hosts and tested for their relative plating ability on strains containing or lacking RII restriction; the presence or absence of SA modification had no effect on RII restriation. In vitro studies revealed, however, that Salmonella DNA is protected against cleavage by purified RII restriction endonuclease (R-EcoRII). This protection is not dependent on SA modification; rather, it appears to be due to methylation by a DNA-cytosine methylase which has overlapping specificity with the RII modification enzyme, but which is not involved in any other known host specificity system.